Subjective assessment of occupational stress and mental health of nurses during the Covid-19 pandemic period - Kowalczuk, Krystyna; Tomaszewska, Katarzyna; Chilińska, Joanna; Krajewska-Kułak, Elżbieta; Sobolewski, Marek; Hermanowicz, Justyna M. (Frontiers in Psychiatry, 2023)
Introduction Health status, sickness absence, and nurses’ attrition have a direct impact on the quality of care provided and patients’ health outcomes. The Covid-19 pandemic exacerbated issues that existed within the Polish healthcare system prior to the pandemic, including staff shortages, low wages, and system inadequacies. The aim of this study was to investigate how nurses during the Covid-19 pandemic period rated the burdensomeness of job characteristics and their mental health status, as well as the correlations between factors directly caused by the Covid-19 pandemic and nurses’ subjective assessments of job characteristics and mental health. Method The cross-sectional study was conducted in January 2022, in Poland and involved 796 registered nurses working in hospitals. Results Despite the pandemic’s sweeping societal effects, this research finds limited alteration in nurses’ perceptions of job stress and self-assessed mental health. Factors such as contact with infected patients, quarantine, and isolation do not appear to substantially modify mental health perceptions among nurses. Intriguingly, nurses subjected to COVID-19 testing report heightened stress and compromised mental health. Conclusion The interplay of diverse factors influencing the well-being of nurses is intricately complex. It is advisable to prudently execute interventions and strategies to address the pandemic, aiming to alleviate its potential adverse effects on the mental health of nurses.